Aspiration Risk and Respiratory Complications in Patients with Esophageal Atresia - Kovesi, Thomas (Frontiers in Pediatrics, 2017)
Chronic, long-term respiratory morbidity (CRM) is common in patients with a history of repaired congenital esophageal atresia, typically associated with tracheoesophageal fistula (EA/TEF). EA/TEF patients are at high risk of having aspiration, and retrospective studies have associated CRM with both recurrent aspiration and atopy. However, studies evaluating the association between CRM in this population and either aspiration or atopy have reported conflicting results. Furthermore, CRM in this population may be due to other related conditions as well, such as tracheomalacia and/or recurrent infections. Aspiration is difficult to confirm, short of lung biopsy. Moreover, even within the largest evidence base assessing the association between CRM and aspiration, which has evaluated the potential relationship between gastroesophageal reflux and asthma, findings are contradictory. Studies attempting to relate CRM to prior aspiration events may inadequately estimate the frequency and severity of previous aspiration episodes. There is convincing evidence documenting that chronic, massive aspiration in patients with repaired EA/TEF is associated with the development of bronchiectasis. While chronic aspiration is likely associated with other CRM in patients with repaired EA/TEF, this does not appear to have been confirmed by the data currently available. Prospective studies that systematically evaluate aspiration risk and allergic disease in patients with repaired EA/TEF and document subsequent CRM will be needed to clarify the causes of CRM in this population. Given the prevalence of CRM, patients with repaired EA/TEF should ideally receive regular follow-up by multidisciplinary teams with expertise in this condition, throughout both childhood and adulthood.